Prove the change of base formula for logarithms. That is, prove that log_a (x) = log_b (x) / log_b (a).

Firstly, recall the definition of a logarithm: if y = loga(x), then this means that y is the power you have to raise a to, to get x, that is ay = x.Now, we want to introduce a new base, b. Let's take log to base b of both sides of the above equation. We get logb(ay) = logb(x). But remember our rules of logarithms -- we know that ylogb(a) = logb(ay), so we get that ylogb(a) = logb(x).Lastly, divide both sides by logb(a), to obtain: y = logb(x)/logb(a). Aha! Remember we started off by saying that y = loga(x). Therefore, loga(x) = logb(x)/logb(a), and our proof is complete!

Answered by Tom H. Maths tutor

8941 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Integrate with respect to x [x^2]


The curve, C has equation y = 2x^2 +5x +k. The minimum value of C is -3/4. Find the value of k.


If y=cos(3x)cosec(4x), find dy/dx.


How do you differentiate y=x^x?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences